Carpentry (Wheels of learning, 1996)
This exceptionally produced trainee guide features a highly illustrated design, technical hints and tips from industry experts, review questions and a whole lot more! Key content includes: Site Layout One - Distance Measurement and Leveling, Site Layout Two - Angular Measurement, Advanced Roof Systems, Advanced Wall Systems, Advanced Stair Systems, Introduction to Light Equipment, Welding, Commercial Finish Work, Site Preparation, and Introductory Skills for the Crew Leader